The Dingle Dell meteorite: A Halloween treat from the Main Belt - Devillepoix, Hadrien; Sansom, Eleanor; Bland, Phil; Towner, Martin; Cupák, M.; Howie, Robert; Jansen-Sturgeon, T.; Cox, M.; Hartig, Benjamin; Benedix, Gretchen; Paxman, Jonathan (John Wiley & Sons, Inc., 2018)
We describe the fall of the Dingle Dell (L/LL 5) meteorite near Morawa in Western Australia on October 31, 2016. The fireball was observed by six observatories of the Desert Fireball Network (DFN), a continental-scale facility optimized to recover meteorites and calculate their pre-entry orbits. The 30 cm meteoroid entered at 15.44 km s-1, followed a moderately steep trajectory of 51° to the horizon from 81 km down to 19 km altitude, where the luminous flight ended at a speed of 3.2 km s-1. Deceleration data indicated one large fragment had made it to the ground. The four person search team recovered a 1.15 kg meteorite within 130 m of the predicted fall line, after 8 h of searching, 6 days after the fall. Dingle Dell is the fourth meteorite recovered by the DFN in Australia, but the first before any rain had contaminated the sample. By numerical integration over 1 Ma, we show that Dingle Dell was most likely ejected from the Main Belt by the 3:1 mean motion resonance with Jupiter, with only a marginal chance that it came from the ?6 resonance. This makes the connection of Dingle Dell to the Flora family (currently thought to be the origin of LL chondrites) unlikely.